2022
DOI: 10.4014/jmb.2208.08011
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Analysis of Halotolerant Bacterial Strains Martelella soudanensis NC18T and NC20

Abstract: Two novel, halotolerant strains of Martelella soudanensis , NC18 T and NC20, were isolated from deep subsurface sediment, deeply sequenced, and comparatively analyzed with related strains. Based on a phylogenetic analysis using 16S rRNA gene sequences, the two strains grouped with members of the genus Martelella . Here, we sequenced the complete genomes of NC18 T and NC20 to understand the mechanisms of their halotolera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 58 publications
0
1
0
Order By: Relevance
“…In addition, average nucleotide identity (ANI) and in silico DNA–DNA hybridization ( is DDH) analyses were performed through the OrthoANIu algorithm ( http://www.ezbiocloud.net/tools/orthoaniu ) and the Genome-to-Genome Distance Calculator 3.0 ( http://ggdc.dsmz.de/ggdc.php ), respectively [ 36 , 37 ]. If the genomic DNA of two organisms reveals a DDH similarity of less than 70% and an ANI similarity of less than 95%, the species are typically considered distinct, and vice versa [ 38 ].…”
Section: Methodsmentioning
confidence: 99%
“…In addition, average nucleotide identity (ANI) and in silico DNA–DNA hybridization ( is DDH) analyses were performed through the OrthoANIu algorithm ( http://www.ezbiocloud.net/tools/orthoaniu ) and the Genome-to-Genome Distance Calculator 3.0 ( http://ggdc.dsmz.de/ggdc.php ), respectively [ 36 , 37 ]. If the genomic DNA of two organisms reveals a DDH similarity of less than 70% and an ANI similarity of less than 95%, the species are typically considered distinct, and vice versa [ 38 ].…”
Section: Methodsmentioning
confidence: 99%
“…The results showed that Nitriliruptoria harbor similar synthesis systems of solutes, such as trehalose, glutamine, glutamate, and proline, and on the other hand each member of Nitriliruptoria species possesses specific mechanisms, K + influx and efflux, betaine and ectoine synthesis, and compatible solutes transport ( Chen et al, 2020 ). Using whole-genome analysis, the halotolerant strains of Martelella soudanensis , NC18 T and NC20, were predicted to harbor various halotolerant-associated genes, including K + uptake protein, K + transport system, ectoine transport system, glycine betaine transport system, and glycine betaine uptake protein, indicating that strains NC18 T and NC20 might tolerate high salinity through the accumulation of potassium ions, ectoine, glycine betaine ( Lee and Kim, 2022 ). Although these findings help to understand the versatile mechanisms of halotolerance existing in halotolerant microbes, genomic comparisons are usually based on genome-wide searches for homologs of known halotolerance-related genes, such as those involved in K + and Na + influx and efflux and the synthesis and transport of compatible solutes.…”
Section: Genomic Comparisonsmentioning
confidence: 99%